Study results of diagnosis of Maedi-visna disease in sheep - Gurdorj, Soyolmaa; Uranbileg, Nyamdolgor; B, Mungun-Ochir; P, Baararjargal; Sandagdorj, Narantsatsral; Sharav, Tumenjargal; Masashi, Sakurai; Bazartseren, Boldbaatar; Adilbish Аltanchimeg (Mongolian Journal of Agricultural Sciences, 2020)
In order to detect pathological and histopathological findings of Maedi-Visna disease, pulmonary tissues which had lesions and suspected of the lung disease were collected in slaughterhouses near Ulaanbaatar city, Batsumber soum of Tuv province, Ulziit soum of Dornogobi province. PCR was performed to examine the part of gene of Maedi-Visna virus and pulmonary tissue of one sheep was positive. Histopathological examination was conducted on lung and by microscopic investigation, interstitial inflammation and inclusion body in cytoplasm of the alveoli epithelium was determined on the sample as some specific findings of Maedi-Visna infection. Хонинд Маеди-висна өвчин оношилсон дүнгээс Маеди-Висна өвчний өөрчлөлтийг хонины уушгинд илрүүлэх зорилгоор Улаанбаатар хот орчмын мал нядалгааныгазрууд болон Төв аймгийн Батсүмбэр, Дорноговь аймгийн Өлзийт сумаас эмгэгтэй байж болзошгүй хонины уушгины эдийн дээжнүүд цуглуулав. Уушгины эдийн дээжүүдийг Полимеразын гинжин урвал (ПГУ)-аар шинжлэхэд нэг хонины уушгины эдэд тус өвчин үүсгэгчийн өвөрмөц гений хэсэг илэрсэн. Дээжинд хийсэн эмгэг судлал, бичил бүтцийн шинжилгээгээр Маеди-Висна өвчний үед гардаг өвөрмөц өөрчлөлтүүд болох уушгины завсрын эдийн үрэвсэл, цулцангийн ханын хучуур эсэд өвөрмөц оршихуун биенцэр үүссэн болох нь тогтоогдов. Түлхүүр үг: уушгины эд, үлэмж-, бичил өөрчлөлт, уушгины завсрын эдийн үрэвсэл, оршихуун биенцэр